The development of Russian peripheral region. Ecological and geopolitical problems of the region of Caucasian spa resorts - Dmitri Piterski; Marina Rattchina (European Regional Science Association (ERSA), 2003)
The region of Caucasian spa resorts is now one of the most important tourist regions of Russia. Before the collapse of the USSR 7% of the total number of health facilities of this country was situated in this region. The favourable natural recreation conditions, their concentration in a relatively limited territory, the considerable potential of health-resorts and the efficiency of therapeutic treatment provide good perspectives for the further development of a health-resort complex among Caucasian spa towns. But this region also faces numerous problems which could affect its future development. The ecological situation of the region is of special interest from the economic-geographical point of view. Over the last 30 years the total population of the region has considerably increased, because of the development of non-resort activities. During this period the industrial zones in the spa resorts and other towns of the region have also expanded considerably. The industrialisation of this region has initiated a conflict of interests between economic growth, resort development and acceptable living conditions. The bad ecological situation in the region of the Caucasian spa resorts was partly a result of the peculiarities of the regional planning system of the Soviet Union and Russia, namely of the poor track record of the realisation of regional and urban planning. Recent scientific and planning studies suggest a complex of environmental protection measures, which will provide opportunities for the stabilisation of the ecological situation and for the restoration of the region of Caucasian spa resorts region in the future. In this event the region of the Caucasian spa resorts could then be held up as a model of environmental protection among resort and recreation areas, and not only in Russia. Although the region of the Caucasian spa resorts does not directly border on the former Soviet Republics (Georgia), it is located directly in the centre of the northern Caucasus, where the political situation in a series of former autonomous subjects of the Russian Federation, especially in the Chechen Republic is rather pronouncedly incalculable and explosive. For the present, the implementation of the new health-resort concept will only be possible with capital investment (domestic and foreign) and modern technology from abroad. But the limitation factor in this case is the unstable geo-political situation in the Northern Caucasus and the corresponding bad investment climate in this part of Russia.
Keywords: 330